Let f 0 ( x ) = e x , and for all n = 1 , 2 , 3 , 4 , . . . , let f n ( x ) = e f n − 1 ( x ) . If
S = n = 0 ∑ 2 0 1 8 [ ∫ 0 1 [ k = 0 ∏ n f k ( x ) ] d x ]
Then what natural number j satisfies 0 > j times ln ( ln ( ln ( . . . ( ln ( S ) ) . . . ) ) ) ?
Details and Assumptions:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Let's begin by noting the first few f n ( x ) .
f 0 ( x ) = e x , f 1 ( x ) = e e x , f 2 ( x ) = e e e x , f 3 ( x ) = e e e e x , . . .
We can see that f n ( x ) is a power tower of n + 1 e 's with an x topping them off. Let P n ( x ) be the product inside the integral. Then
P n ( x ) = k = 0 ∏ n f k ( x ) = e x e e x e e e x . . . n + 1 e’s e e e . . . x
Notice that d x d n + 1 e’s e e e . . . x = P n ( x ) Then we can rewrite the integral as follows:
∫ 0 1 P n ( x ) d x = ∫ 0 1 d x d n + 1 e’s e e e . . . x d x = ∫ 0 1 d ( n + 1 e’s e e e . . . x ) = n + 1 e’s e e e . . . 1 − n + 1 e’s e e e . . . 0 = n + 1 e’s e e e . . . 1 − n e’s e e e . . . 1
Now, looking at S we get
S = n = 0 ∑ 2 0 1 8 ∫ 0 1 P n ( x ) d x = n = 0 ∑ 2 0 1 8 n + 1 e’s e e e . . . 1 − n e’s e e e . . . 1
Which is a nice telescoping sum! The sum can then be easily be evaluated as S = 2 0 1 9 e’s e e e . . . 1 − 1 = 2 0 1 9 e’s e e e . . . − 1 . The 1 has been dropped since the e 1 at the end of the power tower is simply equal to e . Now note that
2 0 1 9 e’s e e e . . . > 2 0 1 9 e’s e e e . . . − 1 > 2 0 1 8 e’s e e e . . .
And also note that since the natural log is strictly increasing over its domain, applying ln to all three preserves the inequality. Lastly, note that applying ln to any power tower of e e e e . . . e consisting of finitely many e 's removes one from the power tower. Thus, applying ln 2018 times to both sides gives
e > 2 0 1 8 times ln ( ln ( ln ( ln ( . . . ln ( S ) . . . ) ) ) ) > 1 1 > 2 0 1 9 times ln ( ln ( ln ( ln ( . . . ln ( S ) . . . ) ) ) ) > 0 0 > 2 0 2 0 times ln ( ln ( ln ( ln ( . . . ln ( S ) . . . ) ) ) ) > − ∞
And so our answer is 2 0 2 0